A Comparative Study on Personal Deixis of English and Tukang Besi Language - Farah Novianty (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
AbstractThe research is about deixis expression in English and Tukang Besi language. This reasearch attempts to describe types of deixis in English and Tukang Besi language. Descriptive qualitative method is used to reveal the types of deixis that used in English and Tukang besi with contrastive analysis to find out the differences and similarities between personal deixis of English and Tukang Besi language. the total number of subject personal pronouns in English is seven: I, He, She, It, You, We, and They; while in Tukang Besi, there are also seven personal pronouns, they are; yaku,kita, kami, ko'o, komiu, iya, ammai. There are no word which has same meaning with "it" in Tukang Besi. Tukang Besi People only use the name of things directly without use an "it".